Plans for teaching domestic science in the public schools. - Foster, Anna Helen; Streeter, Grace Elizabeth (My University, 1907)
Introduction: It seems almost unnecessary in this age, to give any reason for putting Domestic Science in the schools and yet, even now there are few schools that have this work, in comparing with the number that do not have it. Could the people be made to see the importance of this study - the infinite good it does - there would no longer be a school with out a cooking laboratory. Some one has said, "Education in books is only one third of an education; education in the ways of the world and a knowledge of human nature is another third; and education or training of the will is the other third," This latter third is what the training in Domestic Science does for girls. The girls themselves like the Manual Training. Cooking commends itself to them. It is as natural for little girls to make mud-pies as to play with dolls, for the home making instinct is an essential part of her nature. One great advantage of this training is the effect on the development of the girls character. The character of the teacher has a more direct influence because of the more intimate contact of teacher and pupil. It is one way to make the earnest girl into a good citizen, the happy home maker and the capable friend, because when a woman holds in her grasp ability to do her own especial task deftly, easily and rapidly then there will be time for her to exercise, read and think. The study of Domestic Science encourges original thought on the part of the pupil. It gives physical activity, change of position, change of interest, change in form of mental activity, and the pupil goes from it, to her other tasks refreshed instead of wearied and better able to do more in the field of the common branches.
Citation: Foster, Anna Helen and Streeter, Grace Elizabeth. Plans for teaching domestic science in the public schools.. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Domestic Science; Education; Public Schools; Curriculum; Theses